2012
DOI: 10.1177/1099800412440498
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Stage Assessment Using Power Spectral Indices of Heart Rate Variability With a Simple Algorithm

Abstract: Clinical researchers do not typically assess sleep with polysomnography (PSG) but rather with observation. However, methods relying on observation have limited reliability and are not suitable for assessing sleep depth and cycles. The purpose of this methodological study was to compare a sleep analysis method based on power spectral indices of heart rate variability (HRV) data to PSG. PSG and electrocardiography data were collected synchronously from 10 healthy women (ages 20–61 years) over 23 nights i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…56 The longitudinal BCG is a measure of the head-to-foot deflec-57 tions of the body, while the transverse BCG represents antero-58 posterior (or dorso-ventral) vibrations. The original bed-and 59 table-based BCG systems focused on longitudinal BCG mea- 60 surements, representing what was supposed to be the largest 61 projection of the 3-D forces resulting from cardiac ejection 62 [1]. paper.…”
mentioning
confidence: 99%
“…56 The longitudinal BCG is a measure of the head-to-foot deflec-57 tions of the body, while the transverse BCG represents antero-58 posterior (or dorso-ventral) vibrations. The original bed-and 59 table-based BCG systems focused on longitudinal BCG mea- 60 surements, representing what was supposed to be the largest 61 projection of the 3-D forces resulting from cardiac ejection 62 [1]. paper.…”
mentioning
confidence: 99%
“…In other studies [11][12][13], the electromechanical film (Emfit)-based methods showed a slightly higher accuracy than the proposed method, but the kappa value was lower than that of the PVDFbased method [11]. For the four-stage detection, the ECG-based methods [3,4] had lower accuracies and kappa values than the proposed method. The PAT-based method [7] showed a similar kappa value compared with the current study, but the accuracy was lower than that of the proposed method.…”
Section: Resultsmentioning
confidence: 91%
“…For the four-stage detection, the corresponding values were 0.48 and 70.9 %, respectively. As listed in ▶ Redmond [6] Kortelainen [11] Xiao [5] Samy [13] Hwang Hedner [7] Isa [3] Tanida [4] Hwang Table 4 Statistical results of sleep stage detection.…”
Section: Agreement Between the Proposed Methods And Psgmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior RF-based radar systems have demonstrated the feasibility of extracting heart rate from radio signals with Gigahertz of bandwidth. While heart rate is not necessary for sleep apnea diagnosis, we plan to use narrowband sonar transmissions on a smartphone and enable contactless heart rate detection, with the goal of better understanding the sleep architecture [40].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%